2017
DOI: 10.1210/en.2016-1917
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Fc-FGF21 With Improved Resistance to Proteolysis, Increased Affinity Toward β-Klotho, and Enhanced Efficacy in Mice and Cynomolgus Monkeys

Abstract: Fibroblast growth factor (FGF) 21 is a natural hormone that modulates glucose, lipid, and energy metabolism. Previously, we engineered an Fc fusion FGF21 variant with two mutations, Fc-FGF21(RG), to extend the half-life and reduce aggregation and in vivo degradation of FGF21. We now describe a new variant developed to reduce the extreme C-terminal degradation and improve the binding affinity to β-Klotho. We demonstrate, by introducing one additional mutation located at the C terminus of FGF21 (A180E), that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
80
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(87 citation statements)
references
References 27 publications
7
80
0
Order By: Relevance
“…Regardless of the route of administration, long‐term steady levels of circulating FGF21 were obtained in mice treated with AAV‐FGF21 vectors, supporting the absence of anti‐transgene immune responses in these animals. In contrast, humoral responses have been observed shortly after administration of FGF21 analogues to non‐human primates and humans (Adams et al , ; Gaich et al , ; Kim et al , ; Stanislaus et al , ), and the implications of these responses to long‐term drug efficacy are yet unknown. In addition, those FGF21‐class molecules that act as receptor agonists, both in a Klotho‐dependent or in Klotho‐independent manner, may have unpredictable biological effects in vivo .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regardless of the route of administration, long‐term steady levels of circulating FGF21 were obtained in mice treated with AAV‐FGF21 vectors, supporting the absence of anti‐transgene immune responses in these animals. In contrast, humoral responses have been observed shortly after administration of FGF21 analogues to non‐human primates and humans (Adams et al , ; Gaich et al , ; Kim et al , ; Stanislaus et al , ), and the implications of these responses to long‐term drug efficacy are yet unknown. In addition, those FGF21‐class molecules that act as receptor agonists, both in a Klotho‐dependent or in Klotho‐independent manner, may have unpredictable biological effects in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…The pharmaceutical industry is devoting considerable efforts to overcoming these limitations and improving the yield of production of FGF21 analogues or mimetics to enable the development of potential drug products (Zhang & Li, ; So & Leung, ). These FGF21‐class molecules have been reported to have similar therapeutic efficacy than the native FGF21 protein in small and large animal models of obesity and T2D (Foltz et al , ; Hecht et al , ; Adams et al , ; Talukdar et al , ; Stanislaus et al , ). Indeed, first‐generation FGF21 analogues have already reached the clinical stage, and reports from two phase I clinical trials have shown significant improvement of dyslipidemia, slight body weight loss, and reductions in fasting insulinemia in patients with obesity and T2D (Gaich et al , ; Talukdar et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…The recombinant human FGF21 protein used in this study activated down‐stream signalling (phosphorylation of Erk) in HEK293 cells overexpressing pig KLB, with a EC 50 of 2 nM (Figure S1). This is within the same potency range as when human FGF21 was tested in HEK293 overexpressing human KLB …”
Section: Methodsmentioning
confidence: 52%
“…FGF21 and FGF21 analogues have been shown to lower BW in humans and in various animal models . However, the mechanisms behind the weight loss vary among species, from an increase in EE in mice to a decrease in FI in monkeys in several studies, whereas, in humans, it is currently not known whether the observed decrease in BW is driven by a decrease in FI or an increase in EE, or both.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation